Interdisciplinary Contributions to Quality Healthcare: The Impact of Radiology, Nursing, Medical Physics, and Laboratory Teams - Mufti, Mohammed Nabeel Ali; Fallatah, Enas Mohammed; Nasser, Faten Abdullah; Albeladi, Amaal Nafea; Alnakhly, Hajar Mohammed; Alshreef, Ahad Qasim; Alharbi, Rafeeah Hamed; Alshahrani, Aishah Mofrah; Alshahrani, Ameerah Saeed; Hadi, Fai Habib; Fallatah, Eman Mohammed; Alhawsawi, Aeshah Abdulaziz (Journal of Posthumanism, 2024)
Introduction: Good healthcare today depends a lot on teamwork between different specialists. Radiology, nursing, medical physics, and lab teams are all important in making sure that diagnoses are correct, treatments work well, and patients receive complete care. It's important to know how these professionals work together and what each one brings to the table in order to make healthcare services better. Aim of Work: to look at how different healthcare teams like radiology, nursing, medical physics, and lab work together to make healthcare better. It will examine what each team does, how they communicate and work with each other, and how their teamwork affects the results for patients. Methods: The study uses a theoretical, descriptive-analytical method that involves looking at existing literature, scientific articles, and reports from healthcare sources. It looks at existing research and real examples that show how working together among the chosen healthcare areas is important. No research or experiments were done in the field.Results: show that when radiologists, nurses, lab experts, and medical physicists work together, it helps doctors diagnose more accurately, get treatments done faster, and provide more tailored and effective care. However, issues like communication problems, moral questions, and rules from organizations still exist and need big, lasting fixes. Conclusion: The study shows how important it is for different experts to work together in healthcare. Encouraging teamwork, honesty working together, and continuous learning in every part of the organization is essential for providing long-lasting, excellent care.